External Issues Affecting Teachers’ Use of Technology in Saudi Arabia: Systematic Literature Review - Alharbi, Omran; Alotebi, Hatem (Advances in Social Sciences Research Journal, 2019)
External issues have, for many years, had a crucial, adverse, impact upon the extent to which teachers have adopted technology for the promotion of learning, for example by introducing learning management systems (LMS). This problem has particularly affected teachers working in developing and less-developed nations. Despite this, few researchers have conducted systematic literature reviews that explore the Saudi Arabian context. The purpose of this study is to examine and scrutinize what is presented in the academic literature about the external factors that affected teachers use of technology in the teaching process in Saudi universities. The systematic review presented in this paper was carried out using a number of databases. Sources include library resources, key journals, PhD theses, master’s theses, and papers yielded by Google Scholar searches of the relevant literature published from 2008 to 2018. There were 32 studies and just 12 studies included in this systematic review. The findings of this review reveal the current state of those external factors that have for some time delayed and influenced teachers’ use of LMS and associated technologies in their teaching in the Kingdom of Saudi Arabia (KSA) between 2008 and 2018. Recommendations are made in this paper, to help Saudi institutions to limit this phenomenon going forward.